Different perspectives in defining culture - Adelia Hanny Rachman (Universitas Airlangga, 2021)
Society grows and develops rapidly while the theory of culture itself in Indonesia mostly refers to Koentjaraningrat’s paradigm. His theory is basically general and commonly used as a basic examination. The fact concerns me due to its deficiency – less relevant to accommodate currently cultural development. To answer this problem, I pertain to the Ahimsa-Putra’s cultural theory. He proposed his thoughts to a more specific concept of culture. In his article entitled Mendefinisikan Kembali Kebudayaan, Ahimsa-Putra not merely describes definition of culture yet along with its dimensions and elements. This review would like to show whether his theory possibly can stipulate an answer to his criticism towards Koentjaraningrat's theory. Later on, I shall offer my disagreements in some of his views.